2020
DOI: 10.1038/s41467-020-15353-2
|View full text |Cite
|
Sign up to set email alerts
|

A simple contagion process describes spreading of traffic jams in urban networks

Abstract: The spread of traffic jams in urban networks has long been viewed as a complex spatio-temporal phenomenon that often requires computationally intensive microscopic models for analysis purposes. In this study, we present a framework to describe the dynamics of congestion propagation and dissipation of traffic in cities using a simple contagion process, inspired by those used to model infectious disease spread in a population. We introduce two novel macroscopic characteristics of network traffic, namely congesti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…The changes in performance at the onset of, and during the disruption, depend on the specific transport mode and disruption. On most road and pedestrian networks, limitations occur exclusively at links or nodes (prohibiting passage, restricting speed or flow 30 ). Routes (sequences of consecutive links) can be affected if any of their links is affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in performance at the onset of, and during the disruption, depend on the specific transport mode and disruption. On most road and pedestrian networks, limitations occur exclusively at links or nodes (prohibiting passage, restricting speed or flow 30 ). Routes (sequences of consecutive links) can be affected if any of their links is affected.…”
Section: Introductionmentioning
confidence: 99%
“…In the Swiss network, the planned timetable and infrastructure usage of all passenger trains remained the same, with no significant cancellations or adjustments. Nevertheless, the short turning of the long-distance international trains resulted in smaller variability of actual operations, and less entrance delays when entering into the Swiss network at Basel, which hints at a reduced epidemic spreading of delays in a network 30 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…That is because the functions are usually not continuous or differentiable 39 . To efficiently estimate the parameters in the proposed model, we applied a global pattern search algorithm 40 as a derivative-free numerical optimization method to fit the curves for each variable (i.e., f (t) , e(t) , c(t) , and r(t)) 26 . The objective function in this optimization process is the RMSE, which will be minimized by searching for the optimal propagation rate β , recovery rate µ , and exposed rate α .…”
Section: Study Context and Data Collectionmentioning
confidence: 99%
“…Recognizing the limitations of existing models, there is a real need for mathematical models that can capture the spatial-temporal evolution of flooding without relying on a variety of input parameters and historical data such as the volume of waters and the width of the roads. Recent studies have demonstrated a surprisingly significant similarity among spreading processes in different systems, including the spread of traffic congestion in transportation, the contagion of infectious disease in populations, the diffusion of ideas in social networks 25 , as well as the evolution of flooding in urban road networks 26,27 . Motivated by these studies, our goal in this research was to describe the floodwater spreading process using generalized mathematical contagion models, such as classical epidemic models 28 .…”
mentioning
confidence: 99%
“…Airline congestion has been studied via network dynamics like queuing models [ 30 ]. Epidemic spreading process has been recently used to model the spreading of traffic jams in urban networks, assuming both homogeneous infection and recovery rate and homogeneous mixing approximation in network topology [ 31 ]. The possibility of modeling congestion contagion on an airline network using epidemic spreading process has been barely explored, not to mention how to develop a full-fledged heterogeneous spreading model.…”
Section: Introductionmentioning
confidence: 99%